2006
DOI: 10.1016/j.jcrs.2006.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Corneal astigmatism correction with opposite clear corneal incisions or single clear corneal incision: Comparative analysis

Abstract: Paired OCCIs were predictable and effective in providing an enhanced effect for correcting preexisting corneal astigmatism in cataract surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
54
3
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 23 publications
(29 reference statements)
5
54
3
6
Order By: Relevance
“…Lever and Dahan reported 33 patients that 3.5 mm opposite clear corneal incisions straddling the steep axis decreased preexisting astigmatism by a mean value of 2 D. 5 Corresponding figures using this method have been reported to be 1.5D by khokhar et al 10 in our study the difference between the preop median and postop median score was 1D.…”
Section: Limbal Relaxing Incisionssupporting
confidence: 68%
“…Lever and Dahan reported 33 patients that 3.5 mm opposite clear corneal incisions straddling the steep axis decreased preexisting astigmatism by a mean value of 2 D. 5 Corresponding figures using this method have been reported to be 1.5D by khokhar et al 10 in our study the difference between the preop median and postop median score was 1D.…”
Section: Limbal Relaxing Incisionssupporting
confidence: 68%
“…Khokhar et al 12 reported a mean astigmatism correction of 1.66 D at the end of 3 months with OCCI and Nemeth et al reported an astigmatism correction of 1.0 D at the end of 9 weeks with OCCI.…”
mentioning
confidence: 99%
“…In their series of 33 eyes, mean keratometric astigmatism changed from 2.80 D preoperatively to 0.75 D postoperatively.71 Other studies found similar reductions. 72,73 This method is effective for correction of mild to moderate corneal astigmatism, but in eyes with higher degrees of astigmatism it is recommended to use an alternative method or a combination of two or more methods.74 Disadvantages of this method include the increased risk of endophthalmitis due to the penetrating nature of the incisions as compared to non-penetrating methods. For control of leakage in this method nylon sutures may be used for wound closure.…”
Section: Opposite Side Clear Corneal Incision (Occi)mentioning
confidence: 99%